Outcome of a patient with Herlyn-Werner-Wunderlich syndrome treated with Balloon septostomy - pre- and postsurgical ultrasound findings - Dosedla, Erik; Ballová, Zuzana; Gašparová, Petra; Sitáš, Martina; Calda, Pavel (Ceska gynekologie, 2023)
Herlyn-Werner-Wunderlich syndrome is an unusual congenital anomaly defined by a triad of congenital defects of the female urogenital tract - homolateral renal agenesis, uterus duplex and obstructed hemi-hematometrocolpos whose etiology remains still unclear. Pelvic pain, dysmenorrhea and palpable mass due to the hematocolpos or hematometra are the most common clinical symptoms. Endometriosis is considered to be a prevalent finding in these young patients possibly explaining the pathophysiological mechanism of endometriosis as the result of retrograde menstruation. Early diagnosis and subsequent treatment are important to prevent the development of severe complications. In general, clinical and reproductive outcomes after drainage of the hematometrocolpos are reported to be satisfactory. A 13-year-old patient presented with pelvic pain and was diagnosed with OHVIRA syndrome treated with Balloon septostomy.
Keywords: Abnormalities, Multiple; Vagina; Endometriosis; Urogenital Abnormalities; hemi-hematocolpos; Humans; Female; urogenitální abnormality; Mullerian anomaly; lidé; Herlyn-Werner-Wunderlich syndrome; ženské pohlaví; uterus; Pelvic Pain; mladiství; pánevní bolest; Adolescent; vagina; endometrióza; obstructive genital abnormality; Uterus; Wolffian anomaly; mnohočetné abnormality